2008
DOI: 10.1099/vir.0.83543-0
|View full text |Cite
|
Sign up to set email alerts
|

Rapid evolutionary dynamics of zucchini yellow mosaic virus

Abstract: Zucchini yellow mosaic virus (ZYMV) is an economically important virus of cucurbit crops. However, little is known about the rate at which this virus has evolved within members of the family Cucurbitaceae, or the timescale of its epidemiological history. Herein, we present the first analysis of the evolutionary dynamics of ZYMV. Using a Bayesian coalescent approach we show that the coat protein of ZYMV has evolved at a mean rate of 5.0¾10"4 nucleotide substitutions per site, per year. Notably, this rate is equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 35 publications
4
27
1
Order By: Relevance
“…Analysis of the full-length genomic DNA sequences revealed that the level of genetic variation observed in the natural population of TYLCV (1.69×10 -3 subs/site/year) was similar to that found in RNA viruses Simmons et al, 2008;. These and other results suggest that a considerable amount of sequence variation occurs within and between populations of geminiviruses, challenging the view that RNA viruses are prone to higher mutation rates than DNA viruses (Domingo and Holland, 1997;Roossinck, 1997;Isnard et al, 1998;Sanz et al, 1999).…”
Section: Discussionmentioning
confidence: 79%
“…Analysis of the full-length genomic DNA sequences revealed that the level of genetic variation observed in the natural population of TYLCV (1.69×10 -3 subs/site/year) was similar to that found in RNA viruses Simmons et al, 2008;. These and other results suggest that a considerable amount of sequence variation occurs within and between populations of geminiviruses, challenging the view that RNA viruses are prone to higher mutation rates than DNA viruses (Domingo and Holland, 1997;Roossinck, 1997;Isnard et al, 1998;Sanz et al, 1999).…”
Section: Discussionmentioning
confidence: 79%
“…Finally, we observed that all individual luteovirus species appeared within the last 500 years. It is striking that the dates estimated for the majority of these speciation events fall into the same range as those of the Potyviridae and of other families of plant RNA viruses (17,24,43,69). Given this overall similarity in evolutionary patterns, we hypothesize that the intensification of agriculture in the modern era, which resulted in an increase in cultivated plant populations, as well as the establishment of global communication networks, had a major effect on the extent and structure of genetic variation in multiple plant RNA viruses.…”
Section: Discussionmentioning
confidence: 87%
“…For instance, while many rigorous estimates of rates of nucleotide substitution exist for mammalian RNA viruses (e.g. Chen & Holmes, 2006;Hanada et al, 2004;Jenkins et al, 2002;Ramsden et al, 2008), only in the past year have well-supported estimates of substitution rates of plant viruses been published: for the positive-sense singlestranded RNA (ssRNA+) viruses rice yellow mottle virus (Fargette et al, 2008), zucchini yellow mosaic virus (Simmons et al, 2008), a broad group of potyviruses (Gibbs et al, 2008), and the single-stranded DNA (ssDNA) tomato yellow leaf curl virus (TYLCV; . Importantly, these data challenge earlier ideas that plant viruses evolve more slowly than animal viruses (Blok et al, 1987;Fraile et al, 1997) (Jenkins et al, 2002).…”
Section: Introductionmentioning
confidence: 99%